2011
DOI: 10.1007/s11433-011-4489-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise and flow of Zr-based bulk metallic glasses under high shearing stress

Abstract: Deformation of the bulk metallic glasses (BMGs) and the creation and propagation of the shear bands are closely interconnected. Shearing force was loaded on Zr 41.2 Ti 13.8 Cu 12.5 Ni 10.0 Be 22.5 (Vit.1) BMGs by cutting during the turning of the BMG rod. The temperature rise of alloy on the shear bands was calculated and the result showed that it could reach the temperature of the super-cooled liquid zone or exceed the melting point. The temperature rise caused viscous fluid flow and brought about the deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The melting phenomenon caused by the high temperature in the shear zone is also manifested in the chips, and the The cutting temperature in the machining of amorphous alloys also affects the machining performance of amorphous alloys in terms of the shear band. Zhang et al [82] expressed that the deformation of BMG after turning was at least partly caused by the adiabatic shear temperature rise. Increased shear speed leads to significant melting of the workpiece surface due to temperature rise in the shear zone.…”
Section: Machining Performance Of Amorphous Alloysmentioning
confidence: 99%
“…The melting phenomenon caused by the high temperature in the shear zone is also manifested in the chips, and the The cutting temperature in the machining of amorphous alloys also affects the machining performance of amorphous alloys in terms of the shear band. Zhang et al [82] expressed that the deformation of BMG after turning was at least partly caused by the adiabatic shear temperature rise. Increased shear speed leads to significant melting of the workpiece surface due to temperature rise in the shear zone.…”
Section: Machining Performance Of Amorphous Alloysmentioning
confidence: 99%
“…It also indicated that the machining processing of BMG was feasible. Then the in uence of cutting temperature on the generation and propagation of shear band was studied [13]. The results showed that the thermal instability of the shear band was the main reason for the plastic deformation behavior of BMG.…”
Section: Introductionmentioning
confidence: 99%